2018
DOI: 10.1158/1078-0432.ccr-18-0078
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Molecular Profiling of Intrahepatic and Extrahepatic Cholangiocarcinomas: Potential Targets for Intervention

Abstract: Various genetic driver aberrations have been identified among distinct anatomic and clinical subtypes of intrahepatic and extrahepatic cholangiocarcinoma, and these molecular alterations may be prognostic biomarkers and/or predictive of drug response. Tumor samples from patients with cholangiocarcinoma who consented prospectively were analyzed using the MSK-IMPACT platform, a targeted next-generation sequencing assay that analyzes all exons and selected introns of 410 cancer-associated genes. Fisher exact test… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
407
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 423 publications
(438 citation statements)
references
References 28 publications
28
407
3
Order By: Relevance
“…Several studies have identified the different GAs in iCCA and exCCA. The most common mutations in iCCA were found to be IDH1/2, BAP1, KRAS, TP53, SMAD4 and ARID1A, whereas common mutations in exCCA were identified in KRAS, TP53, SMAD4, SKT11, ERBB2, PTEN, ATM and NF1 (10,44). TP53 may play a key role in enabling hepatocyte-derived iCCA (30,18), and KRAS mutations in the absence of TP53 mutations can drive exCCA (41,45).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Several studies have identified the different GAs in iCCA and exCCA. The most common mutations in iCCA were found to be IDH1/2, BAP1, KRAS, TP53, SMAD4 and ARID1A, whereas common mutations in exCCA were identified in KRAS, TP53, SMAD4, SKT11, ERBB2, PTEN, ATM and NF1 (10,44). TP53 may play a key role in enabling hepatocyte-derived iCCA (30,18), and KRAS mutations in the absence of TP53 mutations can drive exCCA (41,45).…”
Section: Discussionmentioning
confidence: 98%
“…Jiao et al (29) discovered frequent inactivating mutations of BAP1, ARID1A and PBRM1, with a high mutation rate in the sequenced tumor. Recently, Lowery et al (10) reported the genome profiling of patients with CCA, including 152 iCCA and 43 exCCA cases, from Caucasian (89.2%, 174/195), Asian (7.1%, 14/195), and African American (3.6%, 7/195) patients, and found that the most common mutations were IDH1, TP53, ARID1A, BAP1, KRAS, PBKM1, SMAD4 and ATM. In the present study, common high frequency mutations (>10%) of TP53, KRAS, SMAD4, TERT, ARID1A and CDKN2A were The top bar graph shows the gene mutation frequency of each sample, the percentages on the left represents the mutation frequency of each mutated gene, and the bar graph on the right shows the number of each mutated gene.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, BAP1 mutations were found to be restricted to iCCA in some studies and BAP1 and IDH mutations were also found in HCC, suggesting an overlap of iCCA, cHCC-CCAs and HCC respectively a common cell-of-origin for at least some of these mass-forming, small-duct type iCCAs. 97,100,101 As cHCC-CCAs represent a separated tumour type, according to the current WHO classification, and mostly vary in their molecular profile significantly to iCCA, this will not be further discussed in this review. 30 Furthermore, TP53 mutations may be used as a surrogate marker for malignancy (eg by immunohistochemistry to discriminate untypical bile duct adenomas (BDA) from iCCA).…”
Section: Molecular Alterations Of Intrahepatic Ccamentioning
confidence: 99%
“…The cancer data was selected by the following criteria: 1) This cancer type is included in the TCGA dataset; 2) The sample size is the largest of its cancer type; and 3) Its source is not from the TCGA. Finally, we obtained a total of 445,249 mutations from 19 cancer types (Armenia, et al, 2018;Bailey, et al, 2016;Dulak, et al, 2013;Imielinski, et al, 2012;Johansson, et al, 2016;Johnson, et al, 2014;Jones, et al, 2014;Kim, et al, 2015;Krauthammer, et al, 2012;Lowery, et al, 2018;Pereira, et al, 2016;Reddy, et al, 2017;Sato, et al, 2013;Schulze, et al, 2015;Soumerai, et al, 2018;Stransky, et al, 2011;Tyner, et al, 2018;Vasaikar, et al, 2019;Wang, et al, 2014), namely TS19 dataset.…”
Section: Mutation Data Collection and Annotationmentioning
confidence: 99%